Morphometric and ultrastructure features of the ventral prostate of rats (Rattus norvegicus) submitted to long-term nicotine treatment - Carvalho, C. A. F.; Favaro, W. J.; Padovani, C. R.; Cagnon, V. H. A. (Blackwell Publishing, 2006)
The harmful effects of nicotine on male genital system fertility have been reported in experimental and clinical studies. However, its effects on prostatic cells and glandular pathogenesis remain unclear. The aim of the present study was to analyse the histological, histochemical and ultrastructural alterations, in addition to stereology, of the ventral lobe of the prostate of rats, submitted to chronic nicotine administration, as well as to establish the relationship between these changes and prostate diseases. Twelve male Wistar rats (Rattus norvegicus) were divided into two experimental groups: group I (nicotine) and group II (control). Samples of the ventral prostate were collected, processed and submitted to histological analysis, acid phosphatase histochemistry and ultrastructural analysis by transmission and scanning electron microscopies. The results showed that in the nicotine group, the secretory epithelial cells of the ventral lobe of the prostate were atrophied, and prostatic intraepithelial neoplasia occurred and reduced the expression of acid phosphatase. The disorganisation of organelles involved in the glandular secretory process, accompanied by biomembrane destructuring, was also observed. In conclusion, nicotine causes drastic alterations in the secretory epithelium of the ventral prostate, compromising its function. Furthermore, nicotine also induces premalignant lesions in the prostate gland, thus representing a risk factor in the development of prostate diseases.
Keywords: nicotine; smoking; stereology; ultrastructure; ventral prostate